Conventional clock drawing tests have low to moderate reliability and validity for detecting subtle cognitive impairments in community-dwelling older adults - Kehl-Floberg, Kristen E.; Marks, Timothy S.; Edwards, Dorothy F.; Giles, Gordon M. (Frontiers in Aging Neuroscience, 2023)
Background Early identification of subtle cognitive decline in community-dwelling older adults is critical, as mild cognitive impairment contributes to disability and can be a precursor to dementia. The clock drawing test (CDT) is a widely adopted cognitive screening measure for dementia, however, the reliability and validity of paper-and-pencil CDT scoring scales for mild cognitive impairment in community samples of older adults is less well established. We examined the reliability, sensitivity and specificity, and construct validity of two free-drawn clock drawing test scales–the Rouleau System and the Clock Drawing Interpretation Scale (CDIS)–for subtle cognitive decline in community-dwelling older adults. Methods We analyzed Rouleau and CDIS scores of 310 community-dwelling older adults who had MoCA scores of 20 or above. For each scale we computed Cronbach’s alpha, receiver operating characteristic curves (ROC) for sensitivity and specificity using the MoCA as the index measure, and item response theory models for difficulty level. Results Our sample was 75% female and 85% Caucasian with a mean education of 16 years. The Rouleau scale had excellent interrater reliability (94%), poor internal consistency [0.37 (0.48)], low sensitivity (0.59) and moderate specificity (0.71) at a score of 9. The CDIS scale had good interrater reliability (88%), moderate internal consistency [0.66 (0.09)], moderate sensitivity (0.78) and low specificity (0.45) at a score of 19. In the item response models, both scales’ total scores gave the most information at lower cognitive levels. Conclusion In our community-dwelling sample, the CDIS’s psychometric properties were better in most respects than the Rouleau for use as a screening instrument. Both scales provide valuable information to clinicians screening older adults for cognitive change, but should be interpreted in the setting of a global cognitive battery and not as stand-alone instruments.